PESTASI HASIL BELAJAR MAHASISWA STAI SANGATTA DALAM MATA KULIAH PERKEMBANGAN PESERTA DIDIK MELALUI METODE PERBERIAN TUGAS DAN METODE DISKUSI PRODI PGMI SMESTER VI TAHUN 2019 - Taufik Hidayat (Al-Rabwah, 2019)
This research has background of job methodology instruction and discus methodology instruction by the teacher of STAI Sangatta. The purpose of this action research will counduct for instruction assesment in the class. This research was counducted in two cycles within 6 month. The phase in each cycle contains planning, action, observation, and reflection. The data were collected through observation, action, documentation, and then the data were analyzed descriptively. The result indcate that job methodology instruction and discus methodology instruction assesment can increase the quality of research job methodology instruction and discus methodology instruction in very good category and the result of item tes of instruction by students is very good category.